2013
DOI: 10.1097/pgp.0b013e318261c35b
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonality of Composite Large-Cell Neuroendocrine Carcinoma and Invasive Intestinal-type Mucinous Adenocarcinoma of the Cervix

Abstract: A rare case of mixed carcinoma of the cervix is reported, composed of a large-cell neuroendocrine carcinoma and an invasive intestinal-type mucinous adenocarcinoma. The large-cell neuroendocrine carcinoma was composed of solid nests, sheets, and trabeculae of medium-sized to large-sized cells, and was positive for chromogranin-A and CD56. The invasive intestinal-type mucinous adenocarcinoma showed sparsely scattered immunoreactivity for chromogranin-A. Using an X-chromosome clonality assay, these 2 components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…CD56 is known to be a less specific neuroendocrine marker compared to chromogranin and synaptophysin [ 11 , 20 , 55 ]. The common coexistence of NEC and epithelial tumors along with the monoclonality of the two components implies a common cellular origin of the neuroendocrine and epithelial components [ 17 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CD56 is known to be a less specific neuroendocrine marker compared to chromogranin and synaptophysin [ 11 , 20 , 55 ]. The common coexistence of NEC and epithelial tumors along with the monoclonality of the two components implies a common cellular origin of the neuroendocrine and epithelial components [ 17 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…An X-chromosome clonality assay showed monoclonality of both components in a case of mixed LCNEC and mucinous carcinoma. This suggests that LCNEC might have arisen from an invasive mucinous adenocarcinoma [ 17 ].…”
Section: Neuroendocrine Tumors Of the Uterine Cervixmentioning
confidence: 99%
See 1 more Smart Citation
“…17 There is evidence that NEC originates from neuroendocrine cells in the endometrium as a result of "divergent differentiation". 9 Yasuoka et al 20 found identical clonality between cervical adenocarcinoma and NEC in an X-chromosome clonality assay. Ariura et al 19 also reported identical alterations in PTEN, PIK3CA and FGFR3 in the endocrine and LCNEC components of NEC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that NEC originates from NE cells of the endometrium and may result from "divergent differentiation" [5]. Yasuoka et al [18] found that both cervical adenocarcinoma and NEC showed identical clonality by using an X-chromosome clonality assay. Such observation suggests that the NEC may arise from the adenocarcinoma through a "dedifferentiation process".…”
Section: Discussionmentioning
confidence: 99%